2019
DOI: 10.1111/jog.14013
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic use of tranexamic acid reduces blood loss and transfusion requirements in patients undergoing cesarean section: A meta‐analysis

Abstract: Aim: Tranexamic acid (TXA) has been used to treat peripartum hemorrhage, while preoperative use of TXA in cesarean section (CS) remains controversial. To assess the effectiveness and safety of prophylactic application of TXA, a meta-analysis was performed. Methods: Electronic databases (MEDLINE [PubMed], Cochrane central register of controlled trials and Embase) were searched up to November 2018. The relevant data and quality of included trail were analyzed by RevMan 5.3. The study was registered at PROSPERO (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 48 publications
0
34
0
2
Order By: Relevance
“…After careful consideration from each authors, we decided to include three studies. [ 19 , 37 , 39 ] All of them were RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After careful consideration from each authors, we decided to include three studies. [ 19 , 37 , 39 ] All of them were RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…Despite clearly stating that the anesthesiologists were blinded, it was not clear who prepared the drugs. [ 39 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antifibrinolytic agent tranexamic acid reduces death in women with postpartum hemorrhage, 28 and for women undergoing cesarian section, its prophylactic use decreases perioperative blood loss and transfusion requirements. 29 It should be emphasized that there is currently a lack of information available regarding the safety or efficacy of antifibrinolytics in feline patients. 30 Using individual measures of hemostatic status, such as platelet concentrations and aPTT, Rivera del Álamo et al 16 found no evidence of changes in coagulation parameters between pregnant cats and non-pregnant cats, or between non-pregnant cats at different stages of their reproductive cycles.…”
Section: Discussionmentioning
confidence: 99%
“…The antifibrinolytic agent tranexamic acid reduces death in women with postpartum hemorrhage, 28 and for women undergoing cesarian section, its prophylactic use decreases perioperative blood loss and transfusion requirements. 29 It should be emphasized that there is currently a lack of information available regarding the safety or efficacy of antifibrinolytics in feline patients. 30 …”
Section: Discussionmentioning
confidence: 99%